Ut figura sit. Beda Czcigodny o tropach Pisma - Ryczek, Wojciech (Vox Patrum, 2018)
The main purpose of the paper is to discuss thirteen tropes presented by the Venerable Bede, a Benedictine monk from the Kingdom of Northumbria, in the manual On figures and tropes (De schematibus et tropis, ca. 710), dedicated to his disciple, Cuthbert. Using the definitions and examples given by Donatus (Ars maior), Bede described thirteen tropes and their variants: metaphor, catachresis, metalepsis, metonymy, antonomasia, epithet, synecdoche (totum a parte, pars a toto), onomatopoeia, periphrasis, hyperbaton (histerologia, anastrophe, parenthesis, tmesis, synchysis), hyperbole, allegory (irony, antiphrasis, enigma, charientism, paremia, sarcasm, asteism), and homoeosis (icon, parable, paradigm). Each of these rhetorical devices was illustrated with examples drawn from the Scripture. Therefore, the categories form the grammatical tradition were transformed into the exegetical means, particularly useful during reading the Bible and discovering its hidden meanings. Deploying tropes for interpretative purposes, Bede proposed the model of exegesis concentrated on both what is signified and the mode of signification.